Luminescent liquid crystals bearing an aggregation-induced emission active tetraphenylthiophene fluorophore. Issue 16 (8th April 2019) - Guo, Ling-Xiang; Xing, Yi-Bo; Wang, Meng; Sun, Ying; Zhang, Xue-Qin; Lin, Bao-Ping; Yang, Hong
Abstract : In this work, six novel luminescent liquid crystal materials bearing an aggregation-induced emission active tetraphenylthiophene fluorophore are described. Abstract : The newly emerging aggregation-induced emission (AIE) theory provides a striking perspective to synthesize luminescent liquid crystal (LLC) materials with outstanding solid-state luminescence properties which have showed potential applications as semiconductor materials, liquid crystal displays and organic light-emitting diodes. However, to date, all the known AIE-active LLC molecules are based on very limited AIE fluorophores including cyanostilbene, tolane, tetraphenylethene and metallomesogen cores, which greatly impede the wide applications of these materials, while on the other hand leave us with plenty of opportunities to develop novel AIE-based LLC materials. In this work, we design and synthesize two categories of tetraphenylthiophene-core disk-like molecules, TPT n bearing one tetraphenylthiophene-core and eight peripheral alkoxyl chains, andTPTE n bearing one tetraphenylthiophene-core and four 3, 4, 5-trialkoxybenzoate groups, which can form square, rectangular or hexagonal columnar phases depending on the mesogenic core structures and the chain length of aliphatic tails. Meanwhile, these tetraphenylthiophene-core LLC molecules exhibit obvious AIE characteristics, the fluorescence emission intensity values measured in the aggregated state were hundred times higher than those values measured in benign solvents. Furthermore, these AIE-active tetraphenylthiophene core LLC materials showed narrow band gap energies and excellent gelation ability in appropriate solvents, due to which they might have potential applications as organic semiconductor materials and sensors.